2022
DOI: 10.1177/08830738221086107
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Levetiracetam and Phenobarbital as First-Line Treatment for Neonatal Seizures

Abstract: High neonatal seizure burden is associated with worsened neurodevelopmental outcomes. We compared the efficacy of initial treatment with levetiracetam vs phenobarbital for maintaining low seizure burden in a retrospective cohort of 25 neonates monitored with video electroencephalography (EEG). Video EEG tracing were reviewed and paired with medication bolus times to determine seizure burden after treatment. Initial cumulative dose of phenobarbital was 20 mg/kg in all but 1 case; initial cumulative dose of leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…A 13 (76%) patients treated with LEV had a sustained seizure burden of 20% compared with 6 (75%) treated with PB. 25 Neonates who received PB showed more reduction in the seizure burden in the hours pre-and post-treatment (24.3 vs 14.2 minutes/hour). However, 6 of 17 (35%) neonates who received LEV remained seizure free after initial treatment, compared with 2 of 8 (25%) neonates who received PB.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…A 13 (76%) patients treated with LEV had a sustained seizure burden of 20% compared with 6 (75%) treated with PB. 25 Neonates who received PB showed more reduction in the seizure burden in the hours pre-and post-treatment (24.3 vs 14.2 minutes/hour). However, 6 of 17 (35%) neonates who received LEV remained seizure free after initial treatment, compared with 2 of 8 (25%) neonates who received PB.…”
Section: Discussionmentioning
confidence: 88%
“…A 13 (76%) patients treated with LEV had a sustained seizure burden of 20% compared with 6 (75%) treated with PB. 25 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the study found that only 26% of premature infants less than 28 weeks could be controlled by LEV (80 mg/kg/day), suggesting that small gestational age is a risk factor for LEV treatment failure 3 . A retrospective study showed that LEV at an initial dose of 50–100 mg/Kg was as effective as PB in controlling neonatal epilepsy (gestational age ≥ 35 weeks) 4 . Liu BK et al found that there was no significant difference in the short‐term efficacy (3 days) between the phenobarbital and levetiracetam group (8–54 mg/kg/d) in the treatment of neonatal epilepsy (gestational age: 38 [38,40] weeks) 5 .…”
mentioning
confidence: 99%